Extended Stochastic Integral and Wick Calculus on Spaces of Regular Generalized Functions Connected with Gamma Measure - Kachanovskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We introduce and study an extended stochastic integral, a Wick product, and Wick versions of holomorphic functions on Kondrat'ev-type spaces of regular generalized functions. These spaces are connected with the Gamma measure on a certain generalization of the Schwartz distribution space \(S'\). As examples, we consider stochastic equations with Wick-type nonlinearity.